Factors affecting technological innovation in shipping industry. - Wang, Xiao. (2010)
Shipping industry can be considered as the oldest global industry; its technological innovation evolves throughout its history and developing rapidly in recent years. As it has been exposed to the competitive environment, this project will study competition as a factor affecting technological innovation in shipping industry, especially from the perspective of shipowners. Even though most shipping companies do not have R&D department, they are the ultimate decision maker on adopting of technological innovation; their competition influences the competition of players in other sectors such as shipyards and equipments makers which also result in technological innovation.